Effects of prolonged running under different environmental conditions on selected physiological markers, muscle damage and time–trial performance in recreational athletes - Suhaimi, Muhammad Zuhaili; Chee, Keong Chen; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Editura Universitatea din Pitesti, 2021)
Problem Statement: Numerous studies have been conducted to improve athletic performance, which is affected by various factors. However, studies on the exercise performance of heat-adapted athletes under different environmental condition is still limited. Approach: Twelve male recreational athletes took part in the present study. The participants underwent prolonged running at the intensity of 70% of their respective VO2max for 60 min. It was then immediately followed by a 20-minutes time–trial performance in a randomized, cross-over trial either in the heat (32°C, 70% relative humidity) or thermoneutral (25°C, 70% relative humidity) environments. The nude body weights of the participants were measured before and after the trials. The participants’ blood samples were obtained before warm-up, at the beginning of exercise, at each 20 minutes and 24 hours after exercise. These samples were examined for changes in plasma volume, plasma lactate and creatine kinase activity. Purpose: This study investigated the effects of prolonged exercise in a hot or thermoneutral environments on different physiological parameters and time–trial performance in recreational athletes. Results: There were no differences between the trials in terms of body weight, plasma lactate, or creatine kinase activity. However, as compared to a thermoneutral environment, the athletes' plasma volume changes and sweat rate were significantly (p < 0.05) higher in the heat trial. The thermoneutral and heat trials had running distances of 3.44 ±0.5 and 3.13 ± 0.5 km, respectively. Conclusion: These findings suggest that running in the heat has no effect on plasma lactate levels or muscle damage. However, the participants' running performance was hampered by the hot and humid conditions